EVALUASI PERUBAHAN KUALITAS TANAH PADA LAHAN BEKAS PENAMBANGAN NIKEL DI PULAU GEBE - Mardi Wibowo (Jurnal Rekayasa Lingkungan)
Since year 1977 until 2005, PT. ANTAM has been exploited nickel ore resources at Gebe Island – Center ofHalmahera District – North Maluku Province. Mining activity, beside give economically advantages also causedegradation of environment quality espicially land quality. Therefore, it need evaluation activity for change ofland quality at Gebe Island after mining activity.From chemical rehabilitation aspect, post mining land and rehabilitation land indacate very lack and lackfertility (base saturated 45,87 – 99,6%; cation exchange capacity 9,43 – 12,43%; Organic Carbon 1,12 –2,31%). From availability of nutrirnt element aspect, post mining land and rehabilitation land indicate verylack and lack fertility (nitrogen 0,1 – 1,19%). Base on that data, it can be concluded that land reclamationactivity not yet achieve standart condition of chemical land.Key words : land quality, post mining lan